2014
DOI: 10.1089/zeb.2014.1013
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Repetitive DNA Library in Parodontidae (Actinopterygii: Characiformes): A Genomic and Evolutionary Approach to the Degeneration of the W Sex Chromosome

Abstract: Repetitive DNA sequences, including tandem and dispersed repeats, comprise a large portion of eukaryotic genomes and are important for gene regulation, sex chromosome differentiation, and karyotype evolution. In Parodontidae, only the repetitive DNAs WAp and pPh2004 and rDNAs were previously studied using fluorescence in situ hybridization. This study aimed to build a library of repetitive DNA in Parodontidae. We isolated 40 clones using C o t-1; 17 of these clones exhibited similarity to repetitive DNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
(67 reference statements)
2
18
0
Order By: Relevance
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 60%
“…The proximal region of FSR is composed of a DNA satellite (sat1WP). In the terminal region, an extensive amount of TE Helitron was verified and, in its whole extension, the FSR is invaded by degenerated TEs of different classes [Schemberger et al, 2014]. Thus, molecular differentiation and erosion of genetic activity of the W chromosome in Parodontidae occurred by accumulation of repetitive sequences of different kinds and classes, which may form domains in the chromatin and have a relation to the expression control of genes present in sex chromosomes and sexual determination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations